Data flow management: why and how. Issue 1 (January 2017) - Graves, Jamie
Abstract : It's hard enough to be constantly on the lookout for the insider threat when you know what you're looking for. It becomes that much more difficult when you don't have a solid idea as to where your data is going, how it is getting there, when it's coming and going and why. Tracking user data movement in and out of your network, through measures such as user authentication to network resources or USB drive monitoring via endpoint data loss prevention (DLP), will greatly enhance your chances of detecting potential data thieves in your environment. It's hard enough to be constantly on the lookout for the insider threat when you know what you're looking for. It becomes more difficult when you don't know where your data is going or how it gets there. Tracking user data movement in and out of your network, through measures such as user authentication to network resources or device monitoring via endpoint data loss prevention (DLP), will greatly enhance your chances of detecting potential data thieves in your environment, explains Jamie Graves of ZoneFox.